The radiosensitizing activity of the SMAC-mimetic, Debio 1143, is TNFα-mediated in head and neck squamous cell carcinoma. Issue 3 (September 2015) - Matzinger, Oscar; Viertl, David; Tsoutsou, Pelagia; Kadi, Linda; Rigotti, Stefania; Zanna, Claudio; Wiedemann, Norbert; Vozenin, Marie-Catherine; Vuagniaux, Grégoire; Bourhis, Jean
Abstract Background and purpose Second mitochondria-derived activator of caspase (SMAC)-mimetics are a new class of targeted drugs that specifically induce apoptotic cancer cell death and block pro-survival signaling by antagonizing selected members of the inhibitor of apoptosis protein (IAP) family. Material and methods The present study was designed to investigate the radiosensitizing effect and optimal sequence of administration of the novel SMAC-mimetic Debio 1143 in vitro and in vivo. Apoptosis, alteration of DNA damage repair (DDR), and tumor necrosis factor-alpha (TNF-α) signaling were examined. Results In vitro, Debio 1143 displayed anti-proliferative activity and enhanced intrinsic radiation sensitivity in 5/6 head and neck squamous cell carcinoma (HNSCC) cell lines in a synergistic manner. In vivo, Debio 1143 dose-dependently radio-sensitized FaDu and SQ20B xenografts, resulting in complete tumor regression in 8/10 FaDu-xenografted mice at the high dose level. At the molecular level, Debio 1143 combined with radiotherapy (RT) induced enhancement of caspase-3 activity, increase in Annexin V-positive cells and karyopyknosis, and increase in TNF-α mRNA levels. Finally, in a neutralization experiment using a TNF-α-blocking antibody and a caspase inhibitor, it was shown that the radiosensitizing effect of Debio 1143 is mediated by caspases and TNF-α. Conclusions These results demonstrate that the novel SMAC-mimetic Debio 1143 is a radiosensitizing agent that is worthy of further investigation in clinical trials in combination with radiotherapy.